Small Snap! Logo Snap! Websites

Work in progress
Snap! C++

Incredible Websites for Incredible People

Proof that 1 + 1 = 3.

Mathematics are very well defined, yet many people do make mistake.

There is a problem:

Let x = y, then

[math]{x} - y + y = y[/math]

[math]\large\frac{ x - y + y }{x - y} = \frac{y}{x - y}[/math]

And how about this one?
[math]\large\frac{10}{2} = 2[/math]

We can then simplify as:

[math]\large\frac{x - y}{x - y} + \large\frac{y}{x - y} = \large\frac{y}{x - y}[/math]

or

[math]{1} + \large\frac{y}{x - y} = \large\frac{y}{x - y}[/math]

[math]{1} = \large\frac{y}{x - y} - \large\frac{y}{x - y}[/math]

[math]{1} = 0[/math]

Now we know that x = y or 1 = 1 is true and that 1 = 0 or 0 = 1 is true, we pose:

0 = 1
1 = 1
1 = 1

Adding these three equations we get:

0 + 1 + 1 = 1 + 1 + 1

or

1 + 1 = 3

You know where the demonstration fails? Post a comment below!